Growing Africa : Unlocking the Potential of Agribusiness - World Bank (World Bank, Washington, DC, 2017)
This report highlights the great potential of the agribusiness sector in Africa by drawing on experience in Africa as well as other regions. The evidence demonstrates that good policies, a conducive business environment, and strategic support from governments can help agribusiness reach its potential. Africa is now at a crossroads, from which it can take concrete steps to realize its potential or continue to lose competitiveness, missing a major opportunity for increased growth, employment, and food security. The report pursues several lines of analysis. First, it synthesizes the large body of work on agriculture and agribusiness in Africa. Second, it builds on a diagnosis of specific value chains. As part of this effort, the value chain for Africa's largest and fastest-growing food import, rice, is benchmarked in Senegal and Ghana against Thailand's rice value chain. Third, 170 agribusiness investments by the Commonwealth Development Corporation (CDC) in Africa and Southeast Asia are analyzed to gain perspective on the elements of success and failure. Fourth, the report synthesizes perspectives from the private sector through interviews with 23 leading agribusiness investors and a number of other key informants. In conclusion, the report offers practical policy advice based on the experience of countries from within and outside Africa. The huge diversity of Africa's agro-ecological, market, and business environments, however, necessarily means that each country (and indeed regions within countries) will need to adapt the broad guidance provided here to the local context. Annex 1, concerning the rice value chain, was authored by John Orchard, Tim Chancellor, Roy Denton, Amadou Abdoulaye Fall, and Peter Jaeger. Annex 2, containing interviews with 23 leading agribusiness players in Africa, was authored by Peter White.